Imagistica statuară a Bisericilor romano-catolice - Munteanu, Marcel Gheorghe (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2019)
Although there is no religious or ecclesial style in the West, the Roman Catholic Church has accepted the presence of religious statues and paintings in worship. The Christological theme is predominant for Christian art and as can be seen in the area of Western art, respec- tively in the space of the Roman Catholic Church it depended on the- ology, but also on the freedom of creators. Subject to the evolution of artistic styles, specific to Western Europe, the sculptures established over the centuries in the Catholic ecclesiastical space, underwent a profound transformation, which meant the loss of liturgical-dogmatic specificity in favor of historicity, plastic narrative and aesthetics.